PENGARUH RELATIONSHIP MARKETING TERHADAP PENINGKATAN PENGUNJUNG PADA HOTEL HARPER PERINTIS MAKASSAR - Rasyid, Muh Nur; Nuhung, Mahmud; Abdullah, Irwan; Pratiwi Hamzah, Ayu Indah (Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze the influence of Relationship Marketing on increasing visitors to the Makassar Pioneer Harper Hotel. The type of research used in the study is simple linear regression. The population in this study were visitors to the Makassar Pioneer Harper Hotel in 2019, and the study sample totaled 99 respondents. The results of this study indicate that the variable relationship marketing can increase the number of visitors at the Makassar Pioneer Harper Hotel because relationship marketing is partially tested with the results of t test of 8,436> t table 1.98472 means that there is an influence between x and y and a significant value of 0,000 <0,05 so that it can be said that there is an effect of variable relationship marketing on the variable increase in visitors.